OXYGEN THERAPY SUPPLY TO HAEMODYNAMIC STATUS IN PATIENT WITH ACUTE MYOCARDIAL INFARCTION - Wulandari, Novita Kurnia; Siswanto, Joni; Widiyati, Sri (Postgraduate Program , Poltekkes Kemenkes Semarang, 2020)
Haemodynamic status which influences to serious condition of AMI. Observing the blood pressure, mean artery pressure, and heart rate are the main parameter of haemodynamic. One of the intervention to AMI patient aim to prevent the expansion of heart attack, also decrease pre-load and after-load with oxygen therapy supply. This study aimed to know the influence oxygen therapy supply to haemodynamic status in patient with AMI in Emergency Instalation of RSUD Dr. Moewardi Surakarta. This study was a Pre Experimental Research with One Group Pre-post Test Design conducted one group of AMI patients who observed in haemodynamic status (blood pressure, mean artery pressure, and heart rate) before and after oxygen therapy supply. Research showed that 30 respondent with systolic (t = 6,662, p value<0,05 is 0,000), dyastolic (Z = -3,763, p value<0,05 is 0,000), mean artery pressure (t = 5,879, p value<0,05 is 0,000), and heart rate (Z = -2,976, p value<0,05 is 0,003). The conclusion showed p value<0,05 so it means that oxygen therapy supply affects haemodynamic status in patient with Acute Myocardial Infarction.Â Â